STUDY OF CLINICAL, RADIOLOGICAL, MICROBIOLOGICAL PROFILE OF COMMUNITY ACQUIRED PNEUMONIA AND CORRELATION WITH PNEUMONIA SEVERITY INDEX - Dr. Channabasavaiah B.V.; Dr. Prithi Gokuldasrao Jadhav; Dr. Sanjay B.C. (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BackgroundCommunity-acquired pneumonia (CAP) is a major cause of morbidity and mortality, particularly in developing countries. Accurate assessment of severity is essential for effective management and prognosis. The Pneumonia Severity Index (PSI) is a validated clinical tool that helps stratify patients based on risk and guide treatment decisions. This study aimed to evaluate the clinical, radiological, and microbiological profile of CAP and to correlate disease severity using the PSI.MethodsA prospective study was conducted on 90 hospitalized CAP patients. Clinical features, comorbidities, laboratory parameters, radiological findings, and sputum culture results were analyzed. Patients were categorized into PSI classes, and associations with clinical and biochemical variables were evaluated statistically.ResultsThe mean age was 54.2 ± 18.3 years with male predominance (57.8%). Cough (77.8%), expectoration (85.6%), and fever (71.1%) were the common symptoms. Diabetes (34.4%) and hypertension (25.6%) were the leading comorbidities. Bilateral pneumonia (36.7%) and right-lower-lobe consolidation (39.1%) were frequent radiological patterns. The mean PSI score was 86.9 ± 25.7, with most patients in Classes III–IV. PSI correlated significantly with age (p < 0.001), socioeconomic status (p = 0.031), hyponatremia (p = 0.006), and altered mental status (p = 0.004). Klebsiella pneumoniae (27.7%) was the predominant pathogen. Clinical improvement occurred in 85.6% of cases, while mortality (4.4%) was confined to PSI Class V.ConclusionThe PSI effectively predicts disease severity and outcomes in CAP. Gram-negative infections, hyponatremia, and multilobar involvement are strong indicators of severe disease. Early PSI assessment with appropriate empirical therapy can reduce complications and mortality.